Gastrointestinal comorbidities in patients with acne vulgaris: A population-based retrospective studyCapsule Summary - Yu-Wen Chen, MD; Chun-Ying Wu, MD, PhD; Yi-Ju Chen, MD, PhD (Elsevier, 2025)
Background: The gut-skin-brain axis has been long postulated in acne vulgaris. Few studies focused on bowel habits in patients with acne vulgaris have yielded controversial results. Objectives: To examine the relationship between acne vulgaris and gastrointestinal comorbidities. Methods: We conducted a nationwide case-control study using data from the Taiwan National Health Insurance Research Database spanning the years 1997 to 2013. Acne vulgaris and the control group were stratified by age, and we examined the association of gastrointestinal comorbidities across different age, sex, and antibiotic use through conditional logistic regression analysis. Results: A total of 185,491 patients with acne vulgaris were identified. The primary demographic for acne vulgaris comprised adolescents, followed by adult-onset groups, with a female predominance observed across all age subgroups. Patients with acne vulgaris exhibited a significantly elevated risk of developing gastrointestinal comorbidities, including peptic ulcers, irritable bowel syndrome, gastroenteritis, gastroesophageal reflux disease, and constipation. This increased risk was particularly notable in patients aged ≥12 years, and those with moderate-to-severe acne. Limitations: Miscoding and misclassification might have occurred. Conclusions: Patients with Acne vulgaris have higher risks of gastrointestinal comorbidities. For patients with moderate-to-severe acne, gastroenterology specialty consultation may be warranted.